PEMBENTUKAN KELAS MENENGAH KOTA: PERAN DAN IMPLIKASI KEBERADAANNYA TERHADAP PERCEPATAN PEMBANGUNAN - Aldwin Surya (JIP ( Jurnal Industri dan Perkotaan ), 2006)
In the globalization era role and existence of urban middle class become more important.In many cases, the urban middle class becomes balancer between upper and lower class.Serious attention upon profession and professionalism shown by urban middle class directlymotivate others to work hard, to be discipline, and to appreciate the ethics and to honorindividual human rights.